2016
DOI: 10.1016/j.athoracsur.2016.03.071
|View full text |Cite
|
Sign up to set email alerts
|

At the Root of the Repair Debate: Outcomes After Elective Aortic Root Replacements for Aortic Insufficiency With Aneurysm

Abstract: Elective root replacement operations in patients younger than 70 are associated with low rates of mortality and reoperation, which should be considered the benchmark operation for aortic valve-sparing or repair operations in similar patients. Worse survival was associated with severe AI and older age, suggesting earlier intervention may be an appropriate therapeutic strategy in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…7 Long-term outcomes are similar with mechanical- versus biological-valved conduit aortic root replacements, even in patients <70 years old. 8…”
Section: Aneurysmsmentioning
confidence: 99%
“…7 Long-term outcomes are similar with mechanical- versus biological-valved conduit aortic root replacements, even in patients <70 years old. 8…”
Section: Aneurysmsmentioning
confidence: 99%
“…Bilkhu and associates reported 1.2% in-hospital mortality in a cohort of 344 patients who underwent root replacement in a large-volume institution [Bilkhu 2016]. Similarly, McCarthy and colleagues described their experience with elective root replacement for aneurysm in a group of 220 patients, and they reported 2% 30-day mortality for patients with severe aortic insufficiency (AI), and 0% mortality for patients with moderate (or less) AI [McCarthy 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Their series was later updated and demonstrated freedom from reoperation of 89.6%±2.9% at ten years, while the percentage of patients with AI grade 1+ increased from 40% to 51%, 2+ from 5% to 11%, 3+ from 0% to 2% and 4+ from 0% to 1% at ten years ( 24 ). McCarthy et al found that long-term survival was impaired in those with preoperative severe AI (HR =2.6, P=0.04) ( 25 ). Deas et al compared eccentric AI jets to concentric jets and found no statistical difference in the cumulative risk of aortic valve replacement at ten years but the absolute numbers, 0% vs. 9.4%, may indicate further study in this area ( 26 ).…”
Section: Vsrr With Severe Aimentioning
confidence: 99%